Media and communication in Asia in early 21st century: Changes, continuities, and challenges - Liu, Jun; Sandvik, Kjetil; Mortensen, Christian Hviid (MedieKultur: Journal of media and communication research, 2017)
Asia has some of the largest, most dynamic, diversified, and complicated media industries in the world (McKinsey & Company, 2015). Entering the 21st Century, the rapid economic and political developments of Asia further energize the growth of media locally and globally (for general discussion, see, e.g., Keane [2006]; Thussu [2006], specific discussions on the cases of Korea [Kim, 2013], Japan [Iwabuchi, 2004], China [Sun, 2009]). In a reflection on the increasing importance of Asian players in global communication industry, Keane describes that “Asianness is colonizing international communications markets” (2006: 839-840) with the impacts ranging from the production of hardware (i.e., East Asian technology) to content (e.g., Japanese manga, anime and TV formats and South Korean popular culture) and from the cross-over of directors and actors from Asia to Hollywood and the world. Yet, a lack of timely understanding of media and communication in a fast-changing Asia is hindering not only our interpretation of the significance of media in social transformation in Asia, but also the efforts to de-westernize (e.g., Park & Curran, 2000; Wang, 2010) or internationalize communication studies (Lee, 2014).